Is Radicalism The Key? Radicalism as A Moderator of The Consequentialist Moral Processing to Support Terrorism - Risnawati, Erna; Wardani, Laila Meiliyandrie Indah; Pratana, Muhammad; Valeria Yekti Kwasaning Gusti; Sa'diah, Siti (DINIKA : Academic Journal of Islamic Studies, 2024)
The fight against terrorism is is complex and multifaceted. Many factors can contribute to support for terrorism, with individual characteristics playing a significant role. Among these characteristics, the process of moral reasoning, pecifically, consequentialist moral processing—greatly influences an individual's decision-making, including their potential support for terrorism. This study explores the relationship between consequentialist moral processing, radicalism, and support for terrorism. 390 respondents were included consisting of 318 male and 72 female, aged 18-45 years, from various religious organizations (Islam, Catholic, Christian, Hindu and Buddhis). The sampling process conducted by Purposive sampling. Measuring instruments used were the Consequentialist Moral Processing questionnaire and a questionnaire in support of terrorism. This study uses a mediation analysis. The results of this study indicate that radicalism plays an effective role as mediator between consequentialist moral processing and support for terrorism. This means that consequentialist moral processing will contribute to supporting terrorism if through radicalism as a mediator. The results of the research become a paradox that radicalism and support for terrorism not only apply to Islamic organizations but also apply to all religious organizations. The results of this study enlighten us on the psychological literature, especially in the case of terrorism.